What a medical school chair wants from the dean - Hromas R; Leverence R; Mramba LK; Jameson JL; Lerman C; Schwenk TL; Zimmermann EM; Good ML (Dove Medical Press, 2018)
Robert Hromas,1 Robert Leverence,1 Lazarus K Mramba,2 J Larry Jameson,3 Caryn Lerman,3 Thomas L Schwenk,4 Ellen M Zimmermann,2 Michael L Good51The Office of the Dean, Department of Medicine, University of Texas Health Science Center San Antonio, San Antonio, TX, USA; 2Department of Medicine, College of Medicine, University of Florida Health, Gainesville, FL, USA; 3Department of Medicine, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, USA; 4Department of Family Medicine, School of Medicine, University of Nevada Reno, Reno, NV, USA; 5Department of Anesthesiology, College of Medicine, University of Florida Health, Gainesville, FL, USAAbstract: Economic pressure has led the evolution of the role of the medical school dean from a clinician educator to a health care system executive. In addition, other dynamic requirements also have likely led to changes in their leadership characteristics. The most important relationship a dean has is with the chairs, yet in the context of the dean’s changing role, little attention has been paid to this relationship. To frame this discussion, we asked medical school chairs what characteristics of a dean’s leadership were most beneficial. We distributed a 26-question survey to 885 clinical and basic science chairs at 41 medical schools. These chairs were confidentially surveyed on their views of six leadership areas: evaluation, barriers to productivity, communication, accountability, crisis management, and organizational values. Of the 491 chairs who responded (response rate =55%), 88% thought that their dean was effective at leading the organization, and 89% enjoyed working with their dean. Chairs indicated that the most important area of expertise of a dean is to define a strategic vision, and the most important value for a dean is integrity between words and deeds. Explaining the reasons behind decisions, providing good feedback, admitting errors, open discussion of complex or awkward topics, and skill in improving relations with the teaching hospital were judged as desirable attributes of a dean. Interestingly, only 23% of chairs want to be a dean in the future. Financial acumen was the least important skill a chair thought a dean should hold, which is in contrast to the skill set for which many deans are hired and evaluated. After reviewing the literature and analyzing these responses, we assert that medical school chairs want their dean to maintain more traditional leadership than that needed by a health care system executive, such as articulating a vision for the future and keeping their promises. Thus, there appears to be a mismatch between what medical school chairs perceive they need from their dean and how the success of a dean is evaluated. Keywords: academic medicine deans, leadership characteristics, organizational values